AKTOR FAKTOR DALAM IMPLEMENTASI KEBIJAKAN PENGADAAN DAN PENYALURAN PUPUK BERSUBSIDI (SUB SEKTOR TANAMAN PANGAN ANGGARAN 2014 DI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR) - Edo, Cici Permata; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Implementation of autonomy development , the regions have the freedom to organize and take care of their own interests that are locality for the implementation of social welfare , Indonesia is an agricultural country that largely livelihoods of farmers . Resources in the District Farmers Rumbio Jaya especially peasant farmers who sought paddy field crops and Horticulture Field starts from hatchery , nursery , and pests which covers the cultivation of crops .This study aims to analyze the process of implementation and the role of actors in the implementation of procurement policies and distribution of subsidized fertilizer in District Rumbio Jaya . The author uses descriptive research method with qualitative approach . While data collection techniques through observation , interview , and documentation . Source of data in this study come from informants in the work environment Riau Provincial Agriculture Office , Agriculture Office Kampar District , District Rumbio Jaya and PT . Riau and Riau Islands PIM , and also informant farmers from Simpang Petai and length ofBased on the research results , we concluded that the problem is caused by the scarcity of fertilizers in addition to natural factors such as availability of raw materials , natural disasters , as well as Farmers have not been fully understood in charging Definitive Plan Needs Farmers Group ( RDKK ) . In terms of implementation , the process of procurement and distribution of subsidized fertilizer has gone well according to the provisions , but the problems that arise in the field is just the technical stuff implementation of the policy . This was due to the cooperation between actors ( farmers , retailers , distributors , manufacturers , and government ) have not been goingPolicy recommendations to the writer suggested , among others, in determining the allocation of central government subsidized fertilizer should consider the proposal made by the needs of farmers and local governments , the need for certainty the type and amount of subsidized fertilizer in the sales package , to consider again the actors involved in the fertilizer distribution network bersubisdi , as well as the necessary improvements in the determination of the person in charge of zoning procurement and distribution of subsidized fertilizer .Keywords : Implementation of policies , subsidized fertilizer , procurement and distribution